Characteristics Of Sn-Zn Cast Alloys With The Addition Of Ag And Cu - Gancarz T. (Archives of Metallurgy and Materials, 2015)
The aim of this work was to study the effects of Ag and Cu on the thermal properties and microstructure of Sn-Zn-Ag-Cu cast alloys. Solders based on eutectic Sn-Zn containing 0.5 to 1.0 at.% of Ag and Cu were developed for wave soldering. DSC measurements were performed to determine the melting temperatures of the alloys. TMA and electrical resistivity measurements were performed between −50 and 150°C and between 30 and 150°C, respectively. Small precipitates of Cu5Zn8, CuZn4, and AgZn3 were observed in the microstructures, and their presence was confirmed by XRD measurements. The inclusion of Ag and Cu improved the electrical resistivity and increased the melting temperature, as well as the CTE, of the alloys. However, tests performed to measure the mechanical properties of the alloys demonstratedthat the addition of Ag and Cu caused the mechanical properties to decrease.